Two new species of Jatropha (Euphorbiaceae) from limestone outcrops in Brazilian seasonally dry tropical forests - Moreira, Ariane Dos Santos; Oliveira, José Florencio Cerqueira; Cordeiro, Inês; Carneiro Torres, Daniela Santos (Phytotaxa, 2020)
We describe and illustrate two new species of Jatropha from Bahia State, Brazil: Jatropha longibracteata and Jatropha paganuccii. The two new species occur on limestone outcrops in seasonally dry tropical forests. We also provide a distribution map and IUCN conservation status, as well as morphological comparisons with the closely related species J. calcarea, J. martiusii, and J. palmatipartita.